Does Customer Satisfaction Mediate the Relationship Between E-Service Quality and Customer Loyalty? myBCA Users Case - Nico Cristian (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines whether customer satisfaction acts as a mediating variable in the relationship between E-Service Quality (e-SQ) and customer loyalty among myBCA users in Indonesia. The research evaluates four dimensions of e-SQ, consisting of efficiency, fulfillment, system availability, and privacy, to identify how each dimension contributes to user satisfaction and loyalty in mobile banking services. A quantitative survey design was applied, and data were collected through an online questionnaire distributed to myBCA users who met the study criteria. A total of 221 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that efficiency and fulfillment significantly enhance customer satisfaction, while system availability and privacy do not show significant effects on satisfaction. In contrast, all four e-SQ dimensions have significant positive effects on customer loyalty. Customer satisfaction, however, does not significantly influence customer loyalty and fails to mediate the relationship between e-SQ dimensions and loyalty. These findings suggest that loyalty toward myBCA is driven more by users’ direct evaluation of service performance than by satisfaction as an intervening factor. The “study contributes to digital banking research by demonstrating that” functional service quality may have a stronger direct role in retaining users than satisfaction in the mobile banking context.